Characterization of the Dynamic Behavior of Neutrophils Following Influenza Vaccination - Pizzagalli, Diego Ulisse; Latino, Irene; Pulfer, Alain; Palomino-Segura, Miguel; Virgilio, Tommaso; Farsakoglu, Yagmur; Krause, Rolf; Gonzalez, Santiago F. (Frontiers in Immunology, 2019)
Neutrophils are amongst the first cells to respond to inflammation and infection. Although they play a key role in limiting the dissemination of pathogens, the study of their dynamic behavior in immune organs remains elusive. In this work, we proposed a novel image-based systems biology approach to characterize in vivo the activities of neutrophils in the mouse popliteal lymph node (PLN) after influenza vaccination with UV-inactivated virus. We described a prominent and rapid recruitment of neutrophils to the LN following vaccination, which is dependent on the secretion of the chemokine CXCL1 and the alarmin molecule IL-1α. In addition, we observed that the initial recruitment occurred mainly via high endothelial venules located in the paracortical and interfollicular regions of the LN. The analysis of the spatial-temporal patterns of neutrophil migration demonstrated that, in the initial stage, the majority of neutrophils display a patrolling behavior, followed by the formation of swarms in the subcapsular sinus of the LN, which are associated with macrophages in this compartment. Finally, we observed using multiple imaging techniques, that neutrophils phagocytize and transport influenza virus particles. These processes might have important implications in the capacity of these cells to present viral antigens.